2019
DOI: 10.1016/j.cois.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prey–predator phenological mismatch under climate change

Abstract: Climate change is disrupting seasonal rhythms and developmental rate of insects  Phenological shifts within and among trophic levels are modifying biotic interactions  Phenological asynchronies contribute to insect communities' restructuration  Disruption of trophic networks affects ecosystem services such as biological control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 97 publications
(84 reference statements)
1
94
0
Order By: Relevance
“…Previous studies have shown that TE may deleteriously affect the behavior and performance of parasitoids in terms of survival, development, flight and host‐finding efficiency, and oviposition behavior (Agosta et al., 2018; Chen, Gols, et al., 2019; Flores‐Mejia et al., 2016; Jerbi‐Elayed et al., 2015). TE exposure has also been shown to affect predator–prey interactions by modifying consumption rate, growth, and behavior, potentially leading to differences in voltinism and phenology, predator population size, and dispersal (Damien & Tougeron, 2019; Jamieson et al., 2012; Sentis et al., 2017).…”
Section: Effects Of Te On Trophic Interactionsmentioning
confidence: 99%
“…Previous studies have shown that TE may deleteriously affect the behavior and performance of parasitoids in terms of survival, development, flight and host‐finding efficiency, and oviposition behavior (Agosta et al., 2018; Chen, Gols, et al., 2019; Flores‐Mejia et al., 2016; Jerbi‐Elayed et al., 2015). TE exposure has also been shown to affect predator–prey interactions by modifying consumption rate, growth, and behavior, potentially leading to differences in voltinism and phenology, predator population size, and dispersal (Damien & Tougeron, 2019; Jamieson et al., 2012; Sentis et al., 2017).…”
Section: Effects Of Te On Trophic Interactionsmentioning
confidence: 99%
“…Such climate-associated phenological change could influence carbon assimilation by modifying the length of the growing season (Keenan et al, 2014;Xia et al, 2015). Differing rates of change in phenology among interacting species result in phenological mismatches between trophic levels (e.g., prey and predator, plant and their pollinators), which affect biotic interactions and community structure (Peñuelas and Filella, 2001;Burkle et al, 2013;Choi et al, 2019;Damien and Tougeron, 2019). Plant phenology also had a feedback effect on climate systems by altering the biophysical attributes of the planet's terrestrial surface and atmospheric structure and composition (Richardson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric changes in the seasonal activities of species between closely interacting sympatric species, such as pollinators and plants, predators and prey, or parasites and hosts, are likely to disrupt the synchronisation of their life cycles (Visser & Both, ; Jeffs & Lewis, ; Ovaskainen et al ., ; Martinez‐Bakker & Helm, ). Such temporal mismatches may lead to complex outcomes in the structure and dynamics of populations and communities (Damien & Tougeron, ). The trophic‐rank hypothesis predicts that organisms from high trophic levels should be more strongly affected by environmental changes and ecological disturbances than organisms from low trophic levels, because of cascading effects in the food chain (Holt et al ., ; Gilman et al ., ).…”
Section: Introductionmentioning
confidence: 99%